2019
DOI: 10.1148/radiol.2019190422
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CT Classification of the Resectability of Pancreatic Cancer: Interobserver Agreement

Abstract: P ancreatic cancer has a dismal prognosis with a 5-year survival rate of only 8% (1). However, surgical resection with a negative margin may be a potentially curative treatment option for this disease. Recently, the concept of borderline resectable pancreatic cancer has emerged to indicate a special category of potential resectability that may help refine the conventional resectable or unresectable binary stratification system (2). Although there is no widespread consensus on the ideal treatment for borderline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 23 publications
4
47
1
1
Order By: Relevance
“…Interestingly, though the interobserver agreement between the radiologists was moderate, their sensitivities were both unsatisfactory. The diagnostic performance of the radiologists was concordant with that of similar studies on CT (16)(17)(18)(19); about 20% of cases were false negative according to the qualitative imaging features. Though a recent study reported that endoscopic ultrasound elastography could improve diagnostic performance of vascular invasion in PDAC, the elastography technique was not commonly used for all patients (28).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Interestingly, though the interobserver agreement between the radiologists was moderate, their sensitivities were both unsatisfactory. The diagnostic performance of the radiologists was concordant with that of similar studies on CT (16)(17)(18)(19); about 20% of cases were false negative according to the qualitative imaging features. Though a recent study reported that endoscopic ultrasound elastography could improve diagnostic performance of vascular invasion in PDAC, the elastography technique was not commonly used for all patients (28).…”
Section: Discussionsupporting
confidence: 65%
“…invasion. Concordance to the previous study, pancreatitis-related changes usually blur the contact region between the solid tumor and adjacent vessels; this led to discrepancy in the interpretation of the degree of tumor-vascular contact (abutment vs encasement, <180°vs >180°, respectively) and may have caused the interobserver variability (19).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Furthermore, the false positive assessment of arterial encasement occurs frequently [11]. Joo et al recently performed a study assessing interrater reliability among radiologists evaluating resectability in PDAC [12]. The authors demonstrated an interrater reliability as low as 30%, and in cases determined as borderline resectable, resection rates varied from 0% to 74%.…”
Section: Discussionmentioning
confidence: 99%